Mortality and acute exacerbation of COPD: a pilot study on the influence of myocardial injury. Issue 6 (29th June 2017) - Laribi, Said; Pemberton, Chris J.; Kirwan, Lyndsey; Nouira, Semir; Turkdogan, Kenan; Yilmaz, Mehmet Birhan; Troughton, Richard W.; Gayat, Etienne; Rivas-Lasarte, Mercedes; Sadoune, Malha; Sabti, Zaid; Hansconrad, Erwin; et al.
Acute exacerbations of chronic obstructive pulmonary disease (COPD) punctuate important disease progression [1]. In-hospital mortality rates for acute exacerbations of COPD vary between 2.5% to 24.5% [2–4]. An integrated clinical score, CURB-65, has been proposed to predict in-hospital and 30-day mortality in acute exacerbations of COPD [5, 6]. According to death-certificate data the most common proximate cause of death in COPD is cardiac disease [7]. An association between elevated cardiac high-sensitivity troponin (hs-cTn) at admission and mortality has been reported in acute exacerbations of COPD [8, 9]. Copeptin has also been associated with poor clinical outcomes and mortality of acute exacerbations of COPD [10], as well as pneumonia [11] and myocardial infarction [12]. Recently, the combination of elevated copeptin and hs-cTn at admission for acute chest pain has been shown to have better discriminative value for acute myocardial injury [13] than troponin alone, as well as strong prognostic value for major cardiac adverse events [14]. We hypothesised that myocardial injury may be an important cause of death in patients admitted with an acute exacerbations of COPD. Accordingly, we investigated whether circulating markers of myocardial injury at the time of presentation to the emergency department (ED) with acute exacerbations of COPD added prognostic value to the CURB-65 score. Acute exacerbated COPD patients with elevated markers of myocardial injury are at high risk of early mortality http://ow.ly/aAaM30adU28